A new approach to determinant factors of local government debt - Ribeiro, Nuno A. (2019)
The purpose of this research is to define a structural/conjunctural model to explain the debt of municipalities. More specifically, the intention is to understand whether there is a relationship between the institutional, tax, budgetary and economic circumstances and municipalities’ debt. The paper fits the theories of debt, namely the theories of public choice, tax illusion and institutional theory, allow identification of a range of factors that can influence municipalities’ debt, using a structural equation methodology. The results allow concluding that the institutional, tax and budgetary situations present a negative and statistically significant relationship with municipal debt. This means that, in the local government setting, when the institutional, tax and budgetary contexts are favourable, debt levels tend to be lower. Therefore, municipalities should take advantage of their institutional context and of periods of higher tax revenue, increased central government grants and investment expenditure, to reduce their debt levels, so they can face other circumstances pushing for debt increases.